2006
DOI: 10.4049/jimmunol.176.6.3516
|View full text |Cite
|
Sign up to set email alerts
|

Complement Receptor 1 and 2 Deficiency Increases Coxsackievirus B3-Induced Myocarditis, Dilated Cardiomyopathy, and Heart Failure by Increasing Macrophages, IL-1β, and Immune Complex Deposition in the Heart

Abstract: Complement and complement receptors (CR) play a central role in immune defense by initiating the rapid destruction of invading microorganisms, amplifying the innate and adaptive immune responses, and mediating solubilization and clearance of immune complexes. Defects in the expression of C or CR have been associated with loss of tolerance to self proteins and the development of immune complex-mediated autoimmune diseases such as systemic lupus erythematosus. In this study, we examined the role of CR on coxsack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 58 publications
0
63
0
1
Order By: Relevance
“…Just as the "over-activation of leucocyte theory" proposed by Rindernech et al [27] , AP aggravates because inflammatory cells are over-activated, and these activated cells such as granulocytes and macrophages, play a great role in the development of AP. Therefore, MPO (the marker of neutrophils) and IL-1β (the inflammatory factors generated mainly by mononuclear macrophages) [28] were detected in this study, indicating that MPO is obviously decreased in pancreas tissue after induction of apoptosis, reducing neutrophil recruition and infiltration to pancreas tissue. IL-1β is a kind of proinflammatory cytokines mainly generated by macrophages in pancreas when AP occurs.…”
Section: Discussionmentioning
confidence: 86%
“…Just as the "over-activation of leucocyte theory" proposed by Rindernech et al [27] , AP aggravates because inflammatory cells are over-activated, and these activated cells such as granulocytes and macrophages, play a great role in the development of AP. Therefore, MPO (the marker of neutrophils) and IL-1β (the inflammatory factors generated mainly by mononuclear macrophages) [28] were detected in this study, indicating that MPO is obviously decreased in pancreas tissue after induction of apoptosis, reducing neutrophil recruition and infiltration to pancreas tissue. IL-1β is a kind of proinflammatory cytokines mainly generated by macrophages in pancreas when AP occurs.…”
Section: Discussionmentioning
confidence: 86%
“…Complement and complement receptors play an important role in both the CVB3-induced and in myosin-induced myocarditis. [27][28][29] ␤1-Adrenoceptor/M2-Receptor ␤1-adrenoceptors (␤1-AR) play an important role in adrenergic regulation of myocardial contractility. They belong to the 7-transmembrane G-protein coupled receptors and stimulation by catecholamines activates the adrenoceptor-adenylylcyclase-protein kinase A cascade (PKA).…”
Section: Induction Of An Immune Response To Auto-antigensmentioning
confidence: 99%
“…Noel Rose and his group recently reported, that an adhesive, fibrotic pericarditis is associated with increased DCM and reduced survival in IFN-g deficient mice following Coxsackievirus B3 infection [49]. The development of fibrosis is an important feature in a number of many pathological conditions including myocarditis, and is a key determinant in the clinical outcome of chronic heart disease [49].…”
Section: Cardiac Troponins and Autoimmune Cardiomyopathymentioning
confidence: 98%
“…Studies to explore the inductive and the effector mechanisms involved in the development of experimental autoimmune myocarditis (EAM) implicate both innate and adaptive immune responses. Important roles have been shown for autoreactive T cells [35], cardiac-specific autoantibodies [15,19], various cytokines and chemokines [32,[40][41][42][43][44][45][46][47], natural killer cells [11], and the complement system [48,49]. Cunningham and her team recently showed that anti-cardiac myosin antibodies target the beta-adrenergic receptor on the surface of the myocytes and induce cAMP-dependent protein kinase A (PKA) activity in the heart cells [50].…”
Section: Cardiac Myosin-induced Autoimmune Myocarditismentioning
confidence: 99%